Crown Ether–Peptide Rotaxanes - Wang, Peng‐Lai; Chen, Peng; Yang, Raorao; Tetlow, Daniel J.; Zhang, Zhi‐Hui; Han, Jing; Fielden, Stephen D. P.; Howlader, Prodip; Zhang, Liang; Leigh, David A. (Angewandte Chemie International Edition, 2025)
We report on the metal‐free active template synthesis of crown ether–peptide rotaxanes. A 24‐crown‐8 ring is sufficiently small that the side chains of canonical branched amino acids act as barriers that trap the macrocycle on the particular glycine residue used to assemble the rotaxane. The resulting crown ether–tripeptide rotaxane can subsequently be extended from either or both N‐ and C‐termini of the axle. Three distinct positional isomers of a heptapeptide [2]rotaxane containing three glycine units were selectively synthesized, and in each case the unique position of the crown ether on the peptide axle was confirmed by 1 H nuclear magnetic resonance spectroscopy and tandem mass spectrometry. The three positional isomers adopt different conformations in the region adjacent to the trapped macrocycle, and have different chemical stabilities and secondary interactions in comparison to the unthreaded peptide axle. The crown ether does not inhibit enzymatic proteolysis over the entire length of the heptapeptide–axle rotaxanes, but rather provides significant protection from degradation for the three to four residues local to the encapsulated region. The strategy opens a pathway to new analogs of naturally occurring mechanically interlocked peptides.